Estimating Labour Supply Elasticities Based on Cross-Country Micro Data: A Bridge Between Micro and Macro Estimates? - Markus Jäntti; Jukka Pirttilä; Håkan Selin (Center for Economic Studies and ifo Institute (CESifo), 2014)
We utilise repeated cross sections of micro data from several countries, available from the Luxembourg Income Study, LIS, to estimate labour supply elasticities, both at the intensive and extensive margin. The benefit of the data is that it spans over four decades and includes a large number of tax reform episodes, with tax rate variation arising both from cross-sectional and country-level differences. Using these data, we investigate whether micro and macro estimates differ in a systematic way. The results do not provide clear support to the view that elasticities at the macro level would be higher than corresponding micro elasticities.
Keywords: E24; H21; J22; 330; labour supply; taxation; cross-country comparisons